Mitochondrial biogenesis and increased uncoupling protein 1 in brown adipose tissue of mice fed a ketone ester diet. - Srivastava, S; Kashiwaya, Y; King, M; Baxa, U; Tam, J; Niu, G; Chen, X; Clarke, K; Veech, R (2012)
We measured the effects of a diet in which D-β-hydroxybutyrate-(R)-1,3 butanediol monoester [ketone ester (KE)] replaced equicaloric amounts of carbohydrate on 8-wk-old male C57BL/6J mice. Diets contained equal amounts of fat, protein, and micronutrients. The KE group was fed ad libitum, whereas the control (Ctrl) mice were pair-fed to the KE group. Blood d-β-hydroxybutyrate levels in the KE group were 3-5 times those reported with high-fat ketogenic diets. Voluntary food intake was reduced dose dependently with the KE diet. Feeding the KE diet for up to 1 mo increased the number of mitochondria and doubled the electron transport chain proteins, uncoupling protein 1, and mitochondrial biogenesis-regulating proteins in the interscapular brown adipose tissue (IBAT). [(18)F]-Fluorodeoxyglucose uptake in IBAT of the KE group was twice that in IBAT of the Ctrl group. Plasma leptin levels of the KE group were more than 2-fold those of the Ctrl group and were associated with increased sympathetic nervous system activity to IBAT. The KE group exhibited 14% greater resting energy expenditure, but the total energy expenditure measured over a 24-h period or body weights was not different. The quantitative insulin-sensitivity check index was 73% higher in the KE group. These results identify KE as a potential antiobesity supplement.